Nitrogen and Pyridine Adsorption on Chromia-Coated Silica and Alumina Catalysts: Probing the Chromia Dispersity - H.M. Ismail; N.E. Fouad; M.I. Zaki (Adsorption Science & Technology, 1991)
Nitrogen and pyridine adsorption studies have been undertaken on variously loaded chromia-coated silica and alumina catalysts. The adsorption data obtained were analyzed with the intention of finding out criteria of relevance to the chromia dispersion. The results have been compared with literature data obtained using a more direct means of investigation. Such comparison showed good agreement which indicates a better dispersion of chromia on alumina than on silica surfaces. This has been tentatively attributed to the different populations and chemistries of the surface hydroxy groups of silica and alumina.